A carbon fiber lamina electrode based on macroporous epoxy with vertical ion channels for structural battery composites. (15th January 2023) - Qi, Guocheng; Cui, Qian; Zhang, Boming; Du, Shanyi
Abstract: Structural battery (SB) composites based on carbon fibers (CFs) are promising multifunctional composite materials to simultaneously realize load-bearing and electrical energy storage. Conventional structural battery electrolytes (SBEs) have bicontinuous phase microstructure characteristics, which makes a further considerable improvement in both mechanical and electrochemical performance of structural batteries rather challenging. Herein, a novel SBE with vertical ion channels in the form of patterned macropores was developed by photolithography based on the UV-initiated cationic polymerization, which was subsequently used in the fabrication of the CF half-cell lamina. The mechanical and electrochemical properties were characterized for both SBE and SB half-cells. The Young's modulus and ionic conductivity of the porous epoxy post-filled with liquid electrolyte were 1.2 GPa and 3.7 mS/cm, respectively, which exceeded the state-of-art multifunctional performances of bicontinuous SBEs. The specific capacity of the SB half-cell could reach 222 ± 10 mAh/g (2nd) at 0.17C, while the tensile modulus of the CF half-cell lamina was 66 ± 4 GPa ( V f  = 22.5 %). This work could provide new insights into a microstructural design for structural batteries towards high multifunctional performances.